Evaluation of in person learning during the pandemic covid-19 - Mohzana Mohzana; Muh. Fahrurrozi; Hartini Hartini (Jurnal Educatio: Jurnal Pendidikan Indonesia)
Government agencies (Education and Culture Office) that are responsible for the learning process play an important role in the evaluation of learning. The purpose of this research is to see the availability of sanitation and hygiene facilities, be able to access health service facilities, readiness to apply mandatory areas for cloth masks or transparent masks for those who have deaf disabilities, have a thermogun (a gunshot body temperature gauge), map education unit residents may not carry out activities in the education unit and make an agreement with the education unit committee regarding the readiness to conduct in person learning in the educational unit. The agreement-making process still needs to apply the Health protocol. Respondents were 115 schools from the element of the principal level of SD / MI and SMP / MTs located in 21 sub-districts in East Lombok district. The results of the study, from 115 instruments obtained the following data as many as 102 respondents with an average value of 86.97 obtained the category "Very Satisfying." Thus as many as 102 schools have completely fulfilled the mandatory provisions in implementing health protocols and equipped supporting facilities according to the provisions. A total of 10 respondents with an average value of 82.82 obtained the "Good" category. Analysis of Offline Mode Simulation of In person Learning during the Covid-19 Pandemic At SD and SMP in East Lombok Regency with 115 schools out of 21 districts in East Lombok Regency, the overall average is 94.65%.